AGRICULTURAL GREEN TOURISM IN UKRAINE: PROBLEMS AND PROSPECTS - Stepanov V.Yu. (Pressing Problems of Public Administration, 2018)
The article is devoted to the consideration of problems and prospects of the development of ruralgreen tourism in Ukraine. The author reveals systemic problems related to state regulation in the fieldof rural green tourism. It is stated that the main task in the formation of this policy is the adoption of arelevant law, coordination of state authorities, as well as public organizations and business structuresfor more effective development of rural green tourism in Ukraine.